Good Country Index – V4 Countries Comparison - Čiefová, Michaela; Natália Goda, (European Journal of Multidisciplinary Studies, 2019)
There are currently many indices ranking countries based on their national competitiveness, happiness, human development and other criteria. A couple of years ago, the Good Country Index was introduced, whose purpose is to measure how a country contributes to the wellbeing of not only its own citizens, but the whole humanity and the planet. The fundamental idea behind the Index is the significant influence of globalisation on spreading both positive and negative trends in the world. Hence it is vital for countries to cooperate in order to handle the negative effects of globalisation. The Index consists of seven dimensions, namely Science - Technology, Culture, International Peace - Security, World Order, Planet - Climate, Prosperity - Equality, and Health - Wellbeing. In the present paper we compare the Index calculations of the Visegrad Group countries and analyse the reasons behind their respective overall positions, as well as ranking within individual sub-indices. Our special attention is dedicated to culture-related phenomena. Based on the analysis, we offer suggestions to improve the current state in the areas where the countries are less successful. The dominant research method utilised is comparative analysis.
Keywords: Good Country Index, comparison, Czech Republic, Hungary, Poland, Slovakia